Keratin Associations with Synthetic, Biosynthetic and Natural Polymers: An Extensive Review - Donato, Ricardo K.; Mija, Alice (Polymers, 2020)
Among the biopolymers from animal sources, keratin is one the most abundant, with a major contribution from side stream products from cattle, ovine and poultry industry, offering many opportunities to produce cost-effective and sustainable advanced materials. Although many reviews have discussed the application of keratin in polymer-based biomaterials, little attention has been paid to its potential in association with other polymer matrices. Thus, herein, we present an extensive literature review summarizing keratin’s compatibility with other synthetic, biosynthetic and natural polymers, and its effect on the materials’ final properties in a myriad of applications. First, we revise the historical context of keratin use, describe its structure, chemical toolset and methods of extraction, overview and differentiate keratins obtained from different sources, highlight the main areas where keratin associations have been applied, and describe the possibilities offered by its chemical toolset. Finally, we contextualize keratin’s potential for addressing current issues in materials sciences, focusing on the effect of keratin when associated to other polymers’ matrices from biomedical to engineering applications, and beyond.